Alterações ecocardiográficas funcionais em pacientes HIV positivos - Freire, Filipe Matheus Barros de Araújo (2019)
With the advent of antiretroviral therapy (ART), HIV infection underwent a major change, becoming a chronic disease and ceasing to be an infection with almost total mortality from opportunistic infections. In this context, other causes of mortality present in the general population have gained prominence in this group of patients, such as neoplastic and cardiovascular diseases. Cardiac involvement occurs in different ways in HIV-positive patients, and HIV-associated myocardial disease (HAMID) is an important manifestation, being present even in those on regular use of HAART. Therefore, this study aimed to evaluate the functional echocardiographic changes found in these individuals, as well as to relate them to the instituted ART. The data of this study were obtained from a cross-sectional study with patients older than 18 years of age from whom clinical data regarding cardiovascular risk, laboratory and clinical data relating to HIV infection and transthoracic Doppler echocardiography were collected. Left ventricular diastolic dysfunction was the most commonly observed alteration, being present in 20 (18.0%) patients, followed by segmental contraction dysfunction of this same chamber, 6 (5.4%) patients, and left ventricular systolic dysfunction in 3 (2.7%). There was no association between the findings and the ART regimen used.